Reflective perspectives of residence heads’ experiences and responses during COVID-19 at a Free State university, South Africa (Journal of Student Affairs in Africa, 2024)
The COVID-19 pandemic affected higher education institutions negatively, especially departments such as Students Affairs at the University of the Free State (UFS) in South Africa. When the national lockdown was announced on 23 March 2020, some students were already in recess and had vacated their residences. Students that had remained were given 72 hours to vacate their residences. By 26 March 2020, the residences were locked, and only a few international and graduate students remained. These changes affected the functioning of residence heads because they had to assume different roles. This reflective article provides perspectives on the experiences and responses of residence heads during the different levels of the COVID-19 lockdown in South Africa and recommendations for future practice and responses of the participating residence heads. The article uses reflective scholarship of practice as a methodology and incorporates Schön’s (1987) reflection as knowing-in-action and further draws on Luescher’s (2018) template for the structure and key components of reflective practice. A focus group discussion was also done to elicit more data from participants. The findings indicate that residence heads experienced anxiety and fear related to their students, families, and jobs during the different lockdown levels. The responses show that effective communication with students and university stakeholders during all levels of the lockdown was key, although confusing and conflicting at times. Most available studies have focused on the experiences and responses of students, teaching and learning, and institutions, but only a few on residence heads during COVID-19. This study provides not only an account of the experiences and responses of residence heads but also recommendations for future residence head practice in student affairs and institutions during similar times of crisis.